Implementasi Logika Fuzzy Tsukamoto Pada Deteksi Kegagalan Sistem Transfer Cake Breaker Conveyor (CBC) - Alkadri Masnur; M.Khairul Anam (Ikatan Ahli Informatika Indonesia, 2018)
The palm Oil Factory is a raw material industry that processes Fresh Fruit Bunches (FFB) into Crude Palm Oil (CPO). Palm oil Factory has a press station in press station has unit Cake Breaker Conveyor (CBC). The CBC to use to transfer dregs and palm shells as fuel bait. For one unit CBC can be serving 4 press machines the waste and oil palm shells to be transferred are still solid clumps due to pressing process is have temperature of 98oC. In addition to the high temperatures of the dregs and the palm oil shells are dense clumps that cause transfer failure In case of transfer failure, the shell and the oil palm dregs will accumulate at the point of disposal of the press machine, other than that the boiler fuel feed is disturbed because the shells and the oil palm dregs are not sent to the fuel furnace. To determine the As Screw break point in the proper position required a method that can find As- screw breaks on the CBC unit. The Fuzzy Tsukamoto logic can help calculate where the As-screw point breaks on the CBC, using the input time and rotation speed of the CBC detection motor using the rotary encoder, the output used is the point where As-screw breaks on a 30 meters. This research is expected to be one solution to solve the problems that occur in the palm oil mill especially in the press station.